Techno comics - Liu, Jia. (2009)
The project aims to develop innovative technology for the production of interactive and resolution independent comics for multiple media such as the web, mobile devices and print. The technology will allow users to collaboratively work on a web comic together and showcase or sell their designs or creation to the whole world. Techno Comics project provides multiple functions include graphic tools and communication clients for users. By using the grapic tools users could make creative comics. By using the communication tools users could instantly work with other cooperators and share all ideas. The integration of a working panel with communication feature will evidently improve the work environment quality and efficiency.